Stasis and Sorting of Americans’ Abortion Opinions: Political Polarization Added to Religious and Other Differences - Michael Hout; Stuart Perrett; Sarah K. Cowan (Socius, 2022)
Americans disagree on legal abortion now about as much as they did in the 1970s, but their attitudes now sort much more according to political identity. Differences of opinion by religion, gender, race, and work that were key to understanding abortion attitudes in the 1970s persisted through 2021. The General Social Survey shows that first conservatives increased their opposition to legal abortion rights; their mean score dropped 1.1 points (on a 6-point scale) from 3.8 to 2.7 from 1974 to 2004. As conservatives’ opinions leveled off, liberals increased their support of abortion rights from 4.7 in 2004 to 5.3 or 5.4 in 2021 (because of Covid-19, survey mode changed, creating uncertainty about the sources of change). Women were significantly more divided by political ideology than men were throughout the time series, but gendered political differences did not displace or reduce religious, educational, racial, or work-life differences.